Revisiting the environmental Kuznets curve in Malaysia: the interactive roles of deforestation and urbanisation. (2018) - Shittu, Waliu Olawale; Musibau, Hammed; Hassan, Sallahuddin
The study re-examines the validity of EKC hypothesis in Malaysia, with the interaction effects of deforestation and urbanisation. The uses of methane and nitro-oxide emissions, as against carbon oxide emissions used in similar studies, also lend credence to the efficiency of the estimates. It employs robust LS, quantile regression and ARDL techniques on secondary data obtained from World Bank and International Energy Agency - from 1981 to 2014. The findings reveal that urbanisation positively and negatively influences the environment; deforestation positively influences it; while the interaction variable enhances the positive effects of each of urbanisation and deforestation on the environment. The study, therefore, recommends, amongst others, increasing incentives for sustainable growth-driven industries - in the forms of tax-cut and lower interest rates to critical sectors, and protection of local ones. The discouragement of forest loss through increased tax, and other penalties, for violators would largely reduce environmental degradation in Malaysia.